Pengaruh Penerapan Kurikulum Merdeka Terhadap Motivasi Belajar Peserta Didik Pada Pembelajaran Bahasa Indonesia Di SMPN 7 Purwokerto - Sabrina Andin Rakhmawati; Laily Nurlina (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to determine the effect of implementing the Merdeka curriculum on the students’ learning motivation in Indonesian language learning at SMPN 7 Purwokerto. It was a quantitative study that employed a survey method. Data collection was conducted through several technique, including questionnaires for students, interviews with Indonesian language teachers, and documentation. The sample in this study consisted of 72 students selected using the Slovin formula. The research results showed that the implementation of the Merdeka curriculum among students at SMPN 7 Purwokerto was positive. It can be seen from the calculation results using SPSS 26 software, which yielded a percentage of 89.4%. this percentage proved that the effect of the Merdeka curriculum on students’ learning motivation was at the coefficient interval level of 0.40-0.599, categorized as moderate.